Intervensi Untuk Menurunkan Kecemasan Keluarga Yang Mendampingi Pasien Kritis Di Intensive Care Unit : Literature Review - Yahya Endra Kristiano; Cecep Eli Kosasih; Aan Nuraeni (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
The family plays an important role in determining the method or treatment needed by the patient in the intensive care unit. However, vulnerable families experience anxiety which will prolong the decision-making process and patient care, so it is very important for nurses to overcome family anxiety so as not to interfere with the functioning of the family's role properly. The purpose of this study was to identify interventions to reduce anxiety in families accompanying patients in the intensive care unit. This research method is a literature review that analyzes articles from five reputable databases, namely Pubmed, CINAHL Plus, Wiley, Science Direct, and Google Scholar with the year of publication of the article between 2016-2021. The keywords used in the article search consisted of 'Patient's family', 'caregivers', 'family', 'therapy', 'anxiety in critical care', and 'fear'. The search results found 11 articles that met the criteria from 85,759 identified articles. The results of the article review identified that interventions that could reduce family anxiety consisted of Aurosoma Therapy, Nurse Social Support, Cognitive Behavioral Therapy (CBT), Spiritual-Religious Intervention, Tele-Mental Health Intervention, Family Integrated Care (FICare), and Nursing Intervention. As well as three interventions that can reduce other psychological symptoms such as depression and stress; Communication Facilitator, Nursing Consultation, and Early Integrated Palliative Care. It is necessary to develop research with a combination of interventions that reduce the level of anxiety in families in Indonesia and be integrated with a critical care setting system to develop comprehensive and holistic nursing care with the patient's family as one of the essential aspects that need to be considered by nursing.